Self-Compassion dan Resilience pada Ibu Bekerja di Tangerang - Kirana, Aulia; Agustini, Agustini; Rahmadanti, Tisah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to determine the relationship between self-compassion and resilience in working mothers in Tangerang. The study was conducted on 180 respondents of working mothers in Tangerang. This research instrument uses a measurement tool of adaptation and modification with a total of 26 items for self-compassion with Cronbach's Alpha of 0.929 and a resilince instrument consisting of 25 items with Cronbach's Alpha of 0.955. The data analysis technique used was the Spearman's Rho correlation test and the results of the data analysis showed that there was a significant positive relationship between self-compasson and resilience with a correlation of (r) 0.635 with a significance value of 0.000. The relationship between the two variables shows that if mothers working in Tangerang have a high level of self-compassion, they can have a high level of resilience.